The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1046/j.1365-2141.2003.04509.x
|View full text |Cite
|
Sign up to set email alerts
|

The IgG subclasses of platelet‐associated autoantibodies directed against platelet glycoproteins IIb/IIIa in patients with idiopathic thrombocytopenic purpura

Abstract: Summary. The majority of patients with idiopathic thrombocytopenic purpura (ITP) have antiplatelet autoantibodies that are most frequently directed against platelet glycoproteins IIb/IIIa or Ib/IX/V. However, there is some debate whether the immune response is oligoclonal or polyclonal in nature. We investigated the subclass distribution of anti-IIb/IIIa IgG autoantibodies in 59 prospectively studied patients with ITP. We also tested patients with a variety of thrombocytopenic disorders (n ¼ 31) and healthy co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 30 publications
(47 reference statements)
3
44
0
Order By: Relevance
“…Patients with ITP have anti-PLT autoantibodies that are most frequently directed against PLT glycoproteins IIb/IIIa or Ib/IX/V. Chan et al (25) reported that the most common subclass of anti-IIb/IIIa antibodies in ITP patients was IgG1. Murase et al (22) reported an IgG subclass of a PLT antibody to be potentially IgG4.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with ITP have anti-PLT autoantibodies that are most frequently directed against PLT glycoproteins IIb/IIIa or Ib/IX/V. Chan et al (25) reported that the most common subclass of anti-IIb/IIIa antibodies in ITP patients was IgG1. Murase et al (22) reported an IgG subclass of a PLT antibody to be potentially IgG4.…”
Section: Discussionmentioning
confidence: 99%
“…An expression level of FcγRII on monocytes was first identified as one of factors associated with H. pylori infection in ITP patients by flow cytometric analysis using a mAb that reacts with both FcγRIIA and FcγRIIB, but this association was later shown to be primarily attributable to inhibitory FcγRIIB based on 2 different assays: quantitative PCR (14,15). It has been shown that anti-GPIIb/IIIa Abs in ITP patients are predominant of the IgG1 subclass (16), which has the highest affinity for FcγRII (13). Thus, FcγRs expressed on macrophages in the RES apparently play a central role in 2 aspects of the pathogenic process: platelet destruction and sustained autoimmune responses to the platelet antigens.…”
Section: Discussionmentioning
confidence: 99%
“…In ITP, an abnormal autoantibody that is usually immunoglobulin G (IgG) with specificity for one or more platelet membrane glycoproteins (GPs) binds to circulating platelet membranes. [10][11][12] In a previous study, it was determined that the PDGF levels are elevated in patients with ITP. 13 In this article, we presented a case that presented both IgAN and ITP, and examine the possible pathophysiological relationship.…”
Section: Introductionmentioning
confidence: 99%